Digital Marketing Dalam Distribusi Ayam Potong Dan Telur Ayam Di Peternakan Nicholas Farm Banyuasin - Dafid, Dafid; Artina, nyimas; Udjulawa, Daniel (FORDICATE, 2024)
The development of science and technology requires almost all fields to adapt to this technology, including the chicken farming business. High human mobility requires the world of trade to be able to provide goods quickly according to consumer demand, in this case broiler and egg. To bridge consumer needs and producer distribution, the right media is needed so that transactions can run well. This service activity aims to provide understanding and skills training to businessman as producers so they can promote and sell their technical products through existing information technology. The method of community service activities is carried out in the form of providing education and training on the use of information technology, especially in the field of digital marketing. The results of this service activity based on questionnaires given to training participants have an impact on business actors in the form of understanding of digital marketing and skills in using and utilizing information technology in the distribution of broiler chickens and chicken eggs.